Wednesday

August 20, 2014

August 20, 2014

Posted by **Anonymous** on Monday, May 7, 2012 at 1:59pm.

6x – 2y = 2

–3x + 4y = 5

- algebra 1 -
**Reiny**, Monday, May 7, 2012 at 2:10pmeasiest way:

double the 2nd, then add that to the first

6y = 12

y = 2

sub back into the 1st

6x - 4 = 2

6x = 6

x = 1

**Related Questions**

algebra - Solve by the linear combination method (with or without multiplication...

algebra - Solve by the linear combination method (with or without multiplication...

algebra - Solve by the linear combination method (with or without multiplication...

algebra - Solve by the linear combination method (with or without multiplication...

algebra - Solve by the linear combination method (with or without multiplication...

Algebra 2 - x+2y+5z=-1 2x-y+z=z 3x+4y-4z=14 solve the system using linear ...

Algebra 2 - how do I solve -15x-2y=-31 4x+6)=11 using linear combination method?

Algebra 1 - Okay. So I am completely lost with this... Any help would be great! ...

math - solve -15x - 2y = -31, 4x + 6y = 11 using Linear Combination Method?

math - solve -15x - 2y = -31, 4x + 6y = 11 using Linear Combination Method?